2019
DOI: 10.32693/jgk.17.1.2019.563
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Vertikal Antara Kelimpahan Foraminifera Dan Karakteristik Sedimen Inti Di Selat Sumba, Nusa Tenggara Timur

Abstract: A B ST RA K Data kelimpahan foraminifera dan karakteristik sedimen inti laut dalam digunakan sebagai proksi untuk merekonstruksi iklim, lingkungan, dan oseanografi di masa lalu. Penelitian ini menggunakan sebuah sampel sedimen inti laut dalam (ST-13) sepanjang 173 cm dari Selat Sumba, Nusa Tenggara Timur. Sampel sedimen tersebut diambil dengan menggunakan Kapal Riset Baruna Jaya VII pada saat Ekspedisi Widya Nusantara (E-WIN) tahun 2016. Sebanyak 22 subsampel sedimen diambil secara vertikal pada setiap interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, only a few studies have identified the abundance and diversity of vertical planktonic foraminifera distribution to determine the marine ecological conditions (i.e. Gustiantini et al, 2015;Ardi et al, 2019;Hendrizan et al, 2019;Damanik et al, 2019;Damanik et al, 2020b;Ardi et al, 2020). A downcore study have also been conducted in Simeulue sub-basin, such as Li et al (2018) who reconstructed the spatiotemporal pattern of sea surface temperature (SST) (Visser et al, 2003), MD98-2170 (Stott et al, 2004), MD98-2165 (Levi et al, 2007) ), MD01-2378 (Xu et al, 2008), MD01-2390 (Steinke et al, 2008), SO139-74 KL (Lückge et al, 2009), GeoB 10038-4, GeoB 10029-4 (Mohtadi et al, 2010), 13GGC (Linsley et al, 2010), SHI9034 (Ding et al, 2013), MD10-3339 (Gustiantini et al, 2015), GEOB10043-3 (Setiawan et al, 2015) , SO184-10043 (Li et al, 2016), BS-36 (Zuraida et al, 2017), BS-24 (Li et al, 2018), ST-13 (Damanik et al, 2019), STA3 (Hendrizan et al, 2019), OS-07 (Damanik et al, 2020a, b), and ST-08 (Ardi et al, 2019(Ardi et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies have identified the abundance and diversity of vertical planktonic foraminifera distribution to determine the marine ecological conditions (i.e. Gustiantini et al, 2015;Ardi et al, 2019;Hendrizan et al, 2019;Damanik et al, 2019;Damanik et al, 2020b;Ardi et al, 2020). A downcore study have also been conducted in Simeulue sub-basin, such as Li et al (2018) who reconstructed the spatiotemporal pattern of sea surface temperature (SST) (Visser et al, 2003), MD98-2170 (Stott et al, 2004), MD98-2165 (Levi et al, 2007) ), MD01-2378 (Xu et al, 2008), MD01-2390 (Steinke et al, 2008), SO139-74 KL (Lückge et al, 2009), GeoB 10038-4, GeoB 10029-4 (Mohtadi et al, 2010), 13GGC (Linsley et al, 2010), SHI9034 (Ding et al, 2013), MD10-3339 (Gustiantini et al, 2015), GEOB10043-3 (Setiawan et al, 2015) , SO184-10043 (Li et al, 2016), BS-36 (Zuraida et al, 2017), BS-24 (Li et al, 2018), ST-13 (Damanik et al, 2019), STA3 (Hendrizan et al, 2019), OS-07 (Damanik et al, 2020a, b), and ST-08 (Ardi et al, 2019(Ardi et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1: Location of sediment cores discussed in this study (black star): MD98-2162(Visser et al, 2003), MD98-2170(Stott et al, 2004), MD98-2165(Levi et al, 2007) ), MD01-2378(Xu et al, 2008), MD01-2390(Steinke et al, 2008), SO139-74 KL(Lückge et al, 2009), GeoB 10038-4, GeoB 10029-4(Mohtadi et al, 2010), 13GGC(Linsley et al, 2010), SHI9034(Ding et al, 2013), MD10-3339(Gustiantini et al, 2015), GEOB10043-3(Setiawan et al, 2015) , SO184-10043(Li et al, 2016), BS-36(Zuraida et al, 2017), BS-24(Li et al, 2018), ST-13(Damanik et al, 2019), STA3(Hendrizan et al, 2019), OS-07(Damanik et al, 2020a, b), and ST-08(Ardi et al, 2019(Ardi et al, , 2020. Sediment location of Core EW17-09 (red star) (modified fromLückge et al, 2009;Mohtadi et al, 2010;Li et al, 2018).…”
mentioning
confidence: 99%